In Vivo and In Vitro Treatment With Edaravone Promotes Proliferation of Neural Progenitor Cells Generated Following Neuronal Loss in the Mouse Dentate Gyrus - Maho Kikuta; Tatsuo Shiba; Masanori Yoneyama; Koichi Kawada; Taro Yamaguchi; Eiichi Hinoi; Yukio Yoneda; Kiyokazu Ogita (Elsevier, 2013)
Edaravone is clinically used in Japan for treatment of patients with acute cerebral infarction. To clarify the effect of edaravone on neurogenesis in the hippocampus following neuronal injury in the hippocampal dentate gyrus, we investigated the effect of in vitro and in vivo treatment with edaravone on the proliferation of neural stem/progenitor cells prepared from the mouse dentate gyrus damaged by trimethyltin (TMT). Histological assessment revealed the presence of large number of nestin(+) cells in the dentate gyrus on days 3 - 5 post-TMT treatment. We prepared cells from the dentate gyrus of naïve, TMT-treated mice or TMT/edaravone-treated mice. The cells obtained from the dentate gyrus of TMT-treated animals were capable of BrdU incorporation and neurosphere formation when cultured in the presence of growth factors. The TMT-treated group had a larger number of nestin(+) cells and nestin(+)GFAP(+) cells than the naïve one. Under the culture condition used, sustained exposure of the cells from the damaged dentate gyrus to edaravone at 10−11 and 10−8 M promoted the proliferation of nestin(+) cells. The systemic in vivo treatment with edaravone for 2 days produced a significant increase in the number of nestin(+) cells among the cells prepared from the dentate gyrus on day 4 post-TMT treatment, and as well as one in the number of neurospheres formed from these cells in the culture. Taken together, our data indicated that edaravone had the ability to promote the proliferation of neural stem/progenitor cells generated following neuronal damage in the dentate gyrus. Keywords:: dentate gyrus, edaravone, neural stem/progenitor cell, neurogenesis, neuronal damage